PENGARUH TINGKAT KEAKTIFAN PENGGUNAAN JEJARING SOSIAL TERHADAP PERILAKU KONSUMTIF SISWA SMAN 9 SURABAYA DALAM BERBELANJA ONLINE - AISYAH DAMAYANTI, NUR (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Iinternet nowadays is one of communication and information media which widely used by the majority of people. Through the Internet, people can accessing the information and communicating in a flexible, fast, and economical. Moreover, anyone can simplify the buying and selling process by online shopping in internet especially social networking. The purpose of this research is to find out the influence of social networking activeness on online shopping consumptive behaviour in SMAN 9 Surabaya students. This research uses a quantitative approach with a population is students of class X and XI which have a social networking accounts and have been online shopping. Total sample are 180 respondents conducted by cluster sampling technique. The data was collected by questionnaires. Simple linear regression, t-test and test for normality was used to analyze the data. The results showed a significant degree of influence between social networking activeness on online shopping consumptive behaviour with t-count value is 2,135 and the significance of value is 0,034. The using level activity of social networking influence of 2.5% on online shopping consumptive behaviour and its in the category of very low. Keywords: social networking, consumptive behavior, online shopping